Non-Bank Financing in Ireland: A Comparative Perspective - O'Toole, Conor M.; Lawless, Martina; Lambert, Derek (The Economic and Social Review, 2015)
This research paper provides a statistical overview of which firms use non-bank financing in Ireland as well as a comparison vis-à-vis other Eurozone countries. We include a wide range of both non-bank debt finance (issued debt, trade credit, loans from friends/family/business partners, mezzanine debt and peer-to-peer lending/crowdfunding) as well as equity finance (venture capital, business angel and equity from friends and family and business partners). We attempt to answer the following research questions: (a) what firm characteristics are correlated with applications for, and usage of, specific types of bank finance? (b) What groups of firms or industries are more likely to apply for and use different types of non-bank finance? (c) Do Irish SMEs differ from other European enterprises and, if so, in what way? This overview should help provide evidence with which to understand the policy options available to diversify the financing options of Irish enterprises beyond their current reliance on bank lending.